PEMAHAMAN TERHADAP GELOMBANG DEMOKRATISASI DUNIA: ANALISA TERHADAP FAKTOR EKONOMI DAN POLITIK SEBAGAI KEKUATAN UTAMA PEMICU PENERAPAN NILAI DEMOKRASI - dewi sucitawathi (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTDuring a democratic wave, the organization of governments is altered – sometimes by peaceful reform, sometimes by dramatic overthrow – in ways that are widely held to be more democratic. During such a democratic wave, there is a great deal of discussion of the virtues of democracy, social movements often demand more democracy, and people in positions of authority proclaim their democratic intentions. During antidemocratic waves, governments are transformed in ways that are widely held to be undemocratic, social movements proclaim their intention to do away with democracy, and government figures proudly express their hostility to democracy.1(Markoff 1996b: 1–2)